PENGARUH TERAPI SUPORTIF KELOMPOK TERHADAP MASALAH MENTAL EMOSIONAL REMAJA - ainil fitri; Meri Neherta; Heppy Sasmita (LPPM Universitas Abdurrab, 2022)
Mental emotional problems at adolescence if not addressed early on can increase the risk of the occurrence of mental disorders. This research aims to know the influence of supportive therapies against mental emotional problems of teenagers. Research conducted at Private Vocational High School of City â€œXâ€. Design of research is Quasy Experimental Pre-Post Test With the Control Group, the sample numbered 108 teens, with the total sampling techniques. 54 the respondent is the intervention group and the 54 respondents again into the control group. The instruments used in this study is questionnaire SDQ (Strengths and Difficulties Questionnaire), module, the workbook, as well as supportive therapy evaluation book groups. Statistical tests are used test t-independent. The research results obtained of a range of mental emotional problems of adolescents in the intervention group prior to the granting of a therapy that is mean: 17,00. After administering therapy obtained the mean: 13, 3. The results meaning that there is a difference of meaning between the emotional mental issues have been given supportive therapy group treatment. The advice of this research is to apply a group of supportive therapy as one therapy to overcome the emotional mental problem experienced by teenagers.